NORCCAP (Norwegian colorectal cancer prevention): a randomised trial to assess the safety and efficacy of carbon dioxide versus air insufflation in colonoscopy. Issue 5 (1st May 2002) - Bretthauer, M; Thiis-Evensen, E; Huppertz-Hauss, G; Gisselsson, L; Grotmol, T; Skovlund, E; Hoff, G
Abstract : Background: To eliminate the risk of combustion during electrosurgical procedures and to reduce patient discomfort, carbon dioxide (CO2 ) insufflation has been recommended during colonoscopy. However, air insufflation is still the standard method, perhaps due to the lack of suitable equipment and shortage of randomised studies. Aims: This randomised controlled trial was conducted to assess patient tolerance and safety when using CO2 insufflation during colonoscopy. Patients: Over an eight month period a successive series of patients referred for a baseline colonoscopy due to findings in a flexible sigmoidoscopy screening trial were randomly assigned to the use of either air or CO2 insufflation during colonoscopy. Methods: End tidal CO2 (ETCO2 ), a non-invasive parameter of arterial pCO2, was registered before and repeatedly during and after the examination. The patient's experience of pain during and after the examination was registered using a visual analogue scale (VAS). Sedation was not used routinely. Results: CO2 insufflation was used in 121 patients (51%) and air in 119 patients (49%). The groups were similar in age, sex, and caecal intubation rate. No rise in ETCO2 was registered. There were statistically significant differences in VAS scores between the groups with less pain reported when using CO2 . Conclusions: This randomised study of unsedated patients shows that CO2 insufflation is safe during colonoscopy with no rise in ETCO2 level. CO2 was found to be superior to air in terms of pain experienced after the examination.